The School Literacy Movement in Elementary School: From Pre-Pandemic to Post-Pandemic Covid-19 - Wijayanti, Sri Hapsari; Baskoro, Josep Tjahjo; Warmiyanti D.W, Maria Tri; Manalu, May Triyanti; Cita, Liza Nur (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The results of the international study on reading literacy show that Indonesian students' reading ability lags far behind other countries. Even nationally, the government measures students' reading literacy levels inadequately. The government initiated the School Literacy Movement (Gerakan Literasi Sekolah/GLS) to increase interest in reading in 2016. The purpose of this study is to describe the implementation of GLS in four elementary schools in Cisauk District, South Tangerang, during the pre-pandemic, pandemic, and post-pandemic covid-19 period. The participants of this study were 17 people, consisting of school principals, teachers, and librarians. This research is descriptive qualitative with data collection techniques in the form of FGDs, interviews, and observation. Data analysis techniques include reducing data, presenting data, and drawing conclusions. This study found that the GLS applied in the four elementary schools is still at the habituation stage of 15 minutes of reading before studying, providing a reading corner, reading in the library, and displaying students' work in wall magazines and classrooms. During the pandemic, students have more opportunities to access readings on the internet to do assignments compared to the pre-pandemic period. In the post-pandemic era, literacy has not been fully revived. Due to a lack of understanding, school principals and teachers have not varied the practice of GLS and still need mentoring.